Estratégias para o crescimento de microempreendedores no mercado local - FRAZÃO, Eliene da Silva; ARAÚJO, Gabriella Nunes de; NASCIMENTO, Júlio César Veríssimo; OLIVEIRA, Victória Fernandes de (191, 2024)
A cidade de Cajamar é um grande centro logístico, o que pode acabar por dificultar o crescimento sustentável dos micros e pequenos empreendedores. Logo, este trabalho tem como finalidade observar e auxiliá-los, propondo a gestão de parcerias, como um meio de estratégia para que possa aumentar seu desenvolvimento, controle e parcerias com outras organizações. Para saber qual a melhor resposta em cada caso, foi efetuado pesquisa com MPE’s na região, pesquisas bibliográficas e estudo de casos, para as melhores possibilidades de soluções, visando como resultado final, o apoio estratégico e gestão de parcerias, desempenham um papel crucial para a sua evolução. A principal hipótese, é a criação de um manual ou desenvolver métricas e modelagem, disponibilizadas e voltadas para o gerenciamento de parcerias nos âmbitos administrativos e financeiros da organização, cujo objetivo, é fazê-las terem um crescimento sustentável, retorno de investimento e margem de lucro, através da disponibilidade de conceitos administrativos, empresas que fizeram sucesso com a implementação de recursos estratégicos e como conseguir parcerias usando esse modelo conceitual, assim, utilizando como meio de estratégia para seu desenvolvimento. PALAVRAS-CHAVE: Microempreendedores; Parcerias, Administração; Estratégias; Crescimento; Gestão.

The city of Cajamar it is a big logistics center, what could end up for making it difficult the sustainable growth of micro and small entrepreneurs. Therefore, this work have the purpose observe and analyze him, proposing partnership management, as a means of strategy for him can increase your development, control, and partnerships with other organizations. To determine the best response in each case, research was conducted with SMEs in the region, along with bibliographic research and case studies to explore the best solution possibilities. The ultimate goal is strategic support and partnership management, which play a crucial role in the organization's evolution. The main hypothesis is the creation of a manual or the development of metrics and modeling focused on partnership management in the administrative and financial areas of the organization. The objective is to foster sustainable growth, return on investment, and profit margin through the availability of administrative concepts, examples of companies that succeeded with the implementation of strategic resources, and guidance on establishing partnerships using this conceptual model, thus employing it as a strategic tool for development.

The city of Cajamar it is a big logistics center, what could end up for making it difficult the sustainable growth of micro and small entrepreneurs. Therefore, this work have the purpose observe and analyze him, proposing partnership management, as a means of strategy for him can increase your development, control, and partnerships with other organizations. To determine the best response in each case, research was conducted with SMEs in the region, along with bibliographic research and case studies to explore the best solution possibilities. The ultimate goal is strategic support and partnership management, which play a crucial role in the organization's evolution. The main hypothesis is the creation of a manual or the development of metrics and modeling focused on partnership management in the administrative and financial areas of the organization. The objective is to foster sustainable growth, return on investment, and profit margin through the availability of administrative concepts, examples of companies that succeeded with the implementation of strategic resources, and guidance on establishing partnerships using this conceptual model, thus employing it as a strategic tool for development.
Strategies for the growth of microentrepreneurs in the local market
Keywords: Empreendedorismo; Gestão e Negócios